Effects of coypu (Myocastor coypus) abundances and diet selection on a wetland of the Patagonian steppe - Galende, Gladys I. (2013)
We assessed diet selection, impact on vegetation, and explored habitat relationships with marsh birds of coypus(Myocastor coypus) in a steppe lagoon in Argentinean Patagonia. In two consecutive springs, abundance and spatial use of the coypus and nesting marsh birds were estimated by direct counts. The coypu was a selective consumer with seasonal variations in food items, and Myriophyllum sp. and Schoenoplectus californicus dominated its diet. Coypus and marsh birds showed a differential spatial use when rushes cover was high. However, when rushes cover decreased by coypu browsing, there was a similar use of space, and marsh birds were displaced to nest on the open water and other poorly protected areas of the rushes. Our results suggest that high abundances of coypu can have a detrimental effect on wetland ecosystems. Systematic monitoring and evaluation of their effects on wetlands in recently colonized areas is recommended.